Analysis of the Role of the Community Movement Program for the Installation of Boundary Markers (GEMAPATAS) in Reducing Land Boundary Disputes in Wonogiri Regency - Arsi Tyas (Semarang State University Undergraduate Law and Society Review, 2025)
The Community Movement for Boundary Marker Installation (GEMAPATAS) Program is a program from the Ministry of ATR/BPN. This program primarily involves community outreach to raise awareness about the importance of installing land boundary markers, along with the free installation of these markers by BPN. After the program's implementation in Wonogiri Regency in 2023, it was found that there was no significant reduction in land boundary disputes. In fact, such disputes remained the most frequently reported land issues by the residents of Wonogiri. This study aims to examine and analyze the implementation and role of the GEMAPATAS Program in reducing land boundary disputes in Wonogiri Regency. The research employs a qualitative method with an empirical juridical approach and descriptive qualitative data analysis techniques. The findings indicate that the GEMAPATAS Program has been implemented fairly well and has received positive responses from the community. For instance, in Pracimantoro Village, one of the program's pilot locations in Wonogiri Regency, the initiative has helped reduce land boundary disputes and increased public awareness about the importance of boundary markers. Additionally, GEMAPATAS has accelerated the implementation of the Complete Systematic Land Registration (PTSL) Program. However, the program has not yet significantly reduced land boundary disputes at the regency level. This is attributed to its limited implementation, covering only 24 villages in Wonogiri Regency, leading to uneven execution. Therefore, it is hoped that the GEMAPATAS Program can be expanded to achieve more optimal results in reducing land boundary disputes in Wonogiri Regency.